ANALYSIS OF FACTORS AFFECTING TAX AVOIDANCE WITH LEVERAGE AS A MEDIATION VARIABLE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2019-2021 PERIOD - Felicia, Jesslyn; Octavia, Jennifer; Engelyne, Elvira; Veronika (Outline Publisher, 2024)
This study aims to analyze the factors that influence tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The factors that are the focus of this study include company size, leverage, profitability, sales growth, institutional ownership, and capital entities. Leverage is identified as a mediating variable in the relationship between these factors and tax avoidance. The population in this study were 398 companies. The sampling method used was purposive sampling and obtained 35 companies that became the object of research. The research data was obtained from the financial reports of manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period.